Association of Chronic Urticaria With Hepatitis C Infection In Female Patients Visiting Tertiary Care Hospital In Pakistan - Sana Waqar Qureshi; Farid ur Rehman; Bilqees Fatima; Kanwal, Shamsa; Sibqa Jamil (Pakistan Armed Forces Medical Journal, 2024)
Objective: To evaluate association of chronic urticaria with hepatitis C infection in female patients. Study Design: comparative cross-sectional study. Place and Duration of Study: Fauji Foundation Hospital Rawalpindi. One-year duration (Jan 2020-Jan 2021). Methodology: One Hundred female patients (group 1) of age 60 years or less with chronic urticaria were enrolled in this study. Patients with chronic liver disease or signs of hepatic decompensation were excluded. Equal number of age and gender matched patients not having urticarial symptoms were selected as group 2. Anti-Hepatitis C Virus Antibody (HCV ab) was evaluated by Enzyme linked immunosorbent assay (ELISA). Disease severity was calculated by Urticaria activity score 7(UAS 7). Association of HCV infection with chronic urticaria and its severity was analyzed by applying appropriate statistical tests. Results: Anti HCV antibody positivity frequency was 14/100(14%) in group 1 and 4/100(4%) in group 2 (p value: 0.013; significant). Mean ages in group 1 and 2 were 39.88+1.38 and 38.79+1.35 years respectively (p value: 0.57; insignificant). Mean UAS 7 calculated in the HCV negative Urticaria cases was 6.73+2.94 while it was significantly higher in HCV positive group i.e. 8.78+6.459 (p value 0.01). Frequency of HCV positivity in patients with well controlled urticaria and mild urticaria was 6/59(10.0%) and 5/36(13.8%) respectively while in moderate urticaria was 3/5(60%) which was significantly higher (p value 0.04). Conclusion: There is a significant association of chronic urticaria with anti HCV antibody positivity. HCV positive patients have more severe disease as compared to HCV negative patients.